Association of H-Type Hypertension with miR-21, miR-29, and miR-199 in Kazahks of Xinjiang, China - Xin He; RuLin Ma; Yu Li; Haixia Wang; YiZhong Yan; YiDan Mao; ShengYu Liao; XueYing Sun; ShuXia Guo; Heng Guo (International Journal of Hypertension)
Objective. This study aims to analyze the expressions of miR-21, miR-29, and miR-199 in the serum of the patients with H-type hypertension among Kazakhs. Then, we analyzed the effect of MTHFR 677C > T polymorphism on the association between the above miRNA and H-type hypertension. Method. In this study, the expression of miR-21, miR-29, and miR-199 was quantitatively measured in 120 serum samples and then stratified according to the C677T polymorphism to analyze the relationship between target miRNAs and HHcy. Results. The expression of miR-21/-29 in the hypertension group was higher than the normal group (P<0.001). And the expression of miR-199 was higher in the hcy group than in the normal group (P<0.001). In the CC and CT genotypes of MTHFR 677C > T, the expression of miR-21 was lower in the HHcy patients than in the normal individuals (P=0.005 and P=0.001) and miR-199 was significantly higher in the HHcy patients than in the normal ones (P=0.002 and P=0.048). No such difference was found in the TT genotype. Logistic regression analysis showed that after adjusting for sex, age, BMI, systolic blood pressure, diastolic blood pressure, and MTHFRC677 T gene polymorphism, miR-21 was negatively correlated with hcy (OR = 0.222, 95% CI (0.101–0.485), P<0.001) and miR-199 was positively correlated with hcy (OR = 1.823,95%CI (1.272∼2.614), P=0.001). Conclusion. miR-21, miR-29, and miR-199 are associated with H-type hypertension in the Kazakhs, especially hyperhomocysteinemia. And these three miRNAs may serve as biomarkers to provide clues to the potential pathogenesis of H-type hypertension.